A Subject Deferred: Exposure and Erasure in an Ethnographic Archive. Issue 3 (13th November 2018) - Fisher, Daniel
ABSTRACT: From as early as the late 1970s anthropologists and ethnomusicologists have been both analysts of and advocates for institutional worlds of Aboriginal art and media. Keenly aware of the Faustian character ascribed to the Indigenous embrace of media, and attuned to the ironies of its governmental subvention, such work of necessity took shape in dialogue with specific institutional possibilities and Australian anxieties. This paper revisits the historical coordinates of Indigenous media research in the age of social media, exploring the relationship between institutional representation and recognition, and the avatars and memes afforded by contemporary social media platforms. Drawing from an ethnographic archive of online media, the essay seeks to better understand the dissimulation and self‐erasure these artefacts entail.